Identification of trigger levels at equilibrium condition for transport mode choice : case study at Klang Komuter Station - Nur Fahriza, Mohd Ali (2016)
This research presents the identification of trigger levels at the equilibrium condition; a condition which users’ decision making on mode choice is balanced when the travel time between bus and car is almost or perfectly equal to each other. The research is conducted at Klang Town where the local authority is planning to construct a new Park and Ride at the Klang Komuter Station. This study chose travel time as an important factor in triggering users’ mode choice either to choose bus or car before embarking on their daily journey and until the users reach their destination. Users often seek for a faster and more convenient method of transportation in getting themselves to reach their destination especially during morning peak hour. The main focus of this research is the trigger levels’ condition that involved in users’ decision making and to investigate the possible choices of decision on the mode of transport whether users will be attracted to switch their mode from car to bus. There are four surveys performed in this study for data collection, namely the Origin-Destination (OD) Survey, Parking Beat Survey, Travel Time Survey, and Revealed Preference/Stated Preference (RP/SP) Survey. The trigger levels were identified by conducting both Graphical and Statistical Analysis. The Statistical Analysis is conducted to validate the results obtained from the Graphical Analysis. The Statistical Analysis was extended to few more steps which are Multiple Linear Regression and Trial and Error Analysis for identification of the trigger levels. There are three equilibrium conditions resulted in this study, which can be applied in order to trigger users to switch mode from car towards bus. The optimum equilibrium condition shows the range of travel time for the bus (26 to 33 minutes) and car (30 to 32 minutes) which indicates the approximately equal of travel time between bus and car. The result of the trigger levels presents the values of travel time for bus and car that almost equal to each other.